Potential health risk assessment of toxic metals contamination in clay eaten as pica (geophagia) among pregnant women of Ho in the Volta Region of Ghana - Akonor, P.T.; Kortei, N.K.; Koryo-Dabrah, A.; Manaphraim, N.Y.B.; Ayim-Akonor, M.; Boadi, N.O.; Essuman, E.K.; Tettey, C. (BMC Pregnancy and Childbirth, 2020)
Introduction: Geophagia although pleasurable and somewhat a necessity among pregnant women, also comes along with its own attendant problems such as exposure to potentially hazardous substances like bacteria, fungi, helminthes and ova, radioactive materials, and toxic elemental minerals in the soil depending on the geographical location. Methodology: This study evaluated the potential health risk involved during the exposure of pregnant women to toxic elemental minerals via the consumption of clay as pica (geophagia). Elemental mineral analysis was carried out using Buck Scientific 210VGP Flame Atomic Absorption Spectrophotometer (Buck Scientific, Inc. East Norwalk, USA). Risk assessment methods were also used to ascertain the various risks factors and the overall risk level. Results: Concentrations of the macro elements investigated were 1.38 ± 1.5, 2.40 ± 1.5, 7.74 ± 1.5, 4.01 ± 1.0, 13.24 ± 2.2 and 13.76 ± 2.1 mg/Kg for iron (Fe), copper (Cu), zinc (Zn), potassium (K), magnesium (Mg) and sodium (Na) respectively. While that for the micro elements were 1.63 ± 0.03 μg/Kg, 4.72 ± 0.8, 0.53 ± 0.02 and 1.85 ± 0.3 mg/kg respectively for arsenic (As), manganese (Mn), lead (Pb) and nickel (Ni). Estimated Daily Intake (EDI), Hazard Quotient (HQ), Target Hazard Quotient (THQ) and Total Target Hazard Quotient (TTHQ) values ranged 0.611–5.44 (mg/kg Bw/ day), 6.26 × 10− 4 – 106.5, 0.067–10.34 and 15 respectively. Conclusion: There is the likelihood of posing adverse health problems when clay samples obtained from Anfoega which is sited in the Volta region of Ghana is consumed due to the fact that the HQ’s of these elemental minerals were > 1 which points to high content of Manganese (Mn) and Nickel (Ni). It is also likely to cause adverse health problems in an individual’s life time since THQ for Arsenic, Lead and Nickel were above 1. Ultimately, the cumulative effect of these toxicants were exceedingly great (≤ 15) which implied a high level of unsafety associated with this clay. Per the results from this study, it is not safe for pregnant women to consume clay as pica since these toxic elements may cause detrimental effects on the foetus of the unborn child.
Research Article
Keywords: Pica; Geophagy; Clay; Volta region; Pregnant women; Risk assessment; Ghana